(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Family anxiety in the Emergency Department (ED) is a psychological problem caused by emergency conditions, uncertainty of patient status, lack of information, and limited communication with health workers. This literature review aimed to identify anxiety management interventions for families of patients in the Emergency Department. The study used a descriptive analytic literature review approach by analyzing articles published between 2021–2026 from Google Scholar, PubMed, and ScienceDirect databases. Literature selection was conducted through identification, screening, eligibility, and inclusion stages, resulting in 8 articles reviewed. The findings showed that triage education, psychoeducation, informational support, therapeutic communication, professional nurse communication, and family-centered care interventions were effective in reducing family anxiety in the ED. The level of patient emergency condition, lack of understanding of the triage system, and inadequate information were identified as factors increasing family anxiety. Effective communication and emotional support from nurses contributed to reducing anxiety and improving family satisfaction with emergency services. Therefore, anxiety management for patient families should be implemented comprehensively through education, communication, and family involvement during emergency care